THE EFFECT OF THE PROBLEM BASED LEARNING (PBL) MODEL ASSISTED BY FLIPBOOK MEDIA ON THE CRITICAL THINKING SKILLS OF STUDENTS IN PRIVATE HIGH SCHOOL PAB 8 SAENTIS CLASS XI ON THE MATERIAL OF THE HUMAN DIGESTIVE SYSTEM: PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTU MEDIA FLIPBOOK TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DI SMA SWASTA PAB 8 SAENTIS KELAS XI PADA MATERI SISTEM PENCERNAAN MANUSIA - Azzahra Ramadhina; Efrida Pima Sari Tambunan (SOSIOEDUKASI, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by flipbook media on students’ critical thinking skills in the topic of the human digestive system at SMA Swasta PAB 8 Saentis. This research employed a quantitative approach with a experimental design in the form of a pretest-posttest control group design. The research sample consisted of two classes: the experimental class, which received learning using the PBL model assisted by flipbook media, and the control class, which received conventional instruction. Data were collected through essay tests (pretest and posttest), observations, interviews, and questionnaires. The data were analyzed using normality, homogeneity, and t-tests with the help of SPSS version 25.0. The results showed a significant difference in the improvement of critical thinking skills between the experimental and control classes. The average posttest score in the experimental class was 78.67, higher than the control class which scored 62.50. The t-test results showed a significance value of 0.000 (p < 0.05), indicating that the PBL model assisted by flipbook media had a significant effect on students’ critical thinking skills. Therefore, it can be concluded that the Problem Based Learning model supported by flipbook media is effective in enhancing students’ critical thinking abilities in biology learning.